INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM TRADISI LISAN SUKU ALAS MELALUI PEMBELAJARAN IPS DI SMP NEGERI 3 LAWE ALAS KUTACANE ACEH TENGGARA - Faadila Reva Alfazira; Fatkhur Rohman; Toni Nasution (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The moral decline among students has emerged as a critical challenge in contemporary education. One potential strategy to address this issue is the internalization of character education values through contextual learning. The oral traditions of the Alas ethnic community, which embody values such as religiosity, honesty, responsibility, mutual cooperation, and social concern, hold significant potential for integration into Social Studies (IPS) learning. This study aims to describe the process of internalizing character education values through the oral traditions of the Alas community in Social Studies instruction, while also identifying its challenges and effectiveness. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation at SMP Negeri 3 Lawe Alas, involving Social Studies teachers, the principal, student affairs personnel, students, and local cultural leaders. The findings reveal that oral traditions, including proverbial advice, traditional poetry, folk songs, syair tangis dilo, and melagam, contain diverse values such as religiosity, honesty, responsibility, cooperation, social empathy, discipline, politeness, respect, and patriotism. These values are internalized through storytelling, discussions, and practical activities, which foster students’ understanding and application of character values. Despite constraints related to limited time, learning media, and teachers’ comprehension of local traditions, this oral tradition–based learning approach proves effective in shaping students’ character.